2023
DOI: 10.1080/10872981.2023.2239453
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fully guided implant planning software training on the knowledge acquisition and satisfaction of dental undergraduate students

Abstract: Background A majority of dental school students do not undergo hands-on clinical training in implantology in the undergraduate curriculum. Training is usually restricted to pre-implant evaluation and post-implant prostheses. Virtual implant planning software (VIPS) provides an alternative opportunity for undergraduate students to experience implant planning much before gaining hands-on experience. However, not many studies have the contribution of VIPS to the knowledge acquisition of students. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The chemotactic function performed by the alpha granules of platelets, particularly by the growth factors contained therein (TGF beta and PDGF), and neo-angiogenic action determine the course of the differentiation of the still-undifferentiated osteoblasts and neo-angiogenesis; these effects serve as the basis of the formation of new bone, whose quality and quantity depend on the outcomes of clots and the platelets they contain. A particularly important role is played by the surgical planning of implant positioning; many authors [46][47][48] have demonstrated how perfect knowledge of the bone anatomy and the consequent guided surgical planning can improve the optimal selection of the implant, reduce surgical times, obtain optimal prosthetic results, and, in what is probably the most important aspect, improve the attitudes of patients to implant surgery. In the future, it will be possible to make complete libraries relating to the Rex implant available to clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…The chemotactic function performed by the alpha granules of platelets, particularly by the growth factors contained therein (TGF beta and PDGF), and neo-angiogenic action determine the course of the differentiation of the still-undifferentiated osteoblasts and neo-angiogenesis; these effects serve as the basis of the formation of new bone, whose quality and quantity depend on the outcomes of clots and the platelets they contain. A particularly important role is played by the surgical planning of implant positioning; many authors [46][47][48] have demonstrated how perfect knowledge of the bone anatomy and the consequent guided surgical planning can improve the optimal selection of the implant, reduce surgical times, obtain optimal prosthetic results, and, in what is probably the most important aspect, improve the attitudes of patients to implant surgery. In the future, it will be possible to make complete libraries relating to the Rex implant available to clinicians.…”
Section: Discussionmentioning
confidence: 99%